2020
DOI: 10.1371/journal.pone.0229819
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF) blocking agents are associated with lower risk for Alzheimer’s disease in patients with rheumatoid arthritis and psoriasis

Abstract: This large, retrospective case-control study of electronic health records from 56 million unique adult patients examined whether or not treatment with a Tumor Necrosis Factor (TNF) blocking agent is associated with lower risk for Alzheimer's disease (AD) in patients with rheumatoid arthritis (RA), psoriasis, and other inflammatory diseases which are mediated in part by TNF and for which a TNF blocker is an approved treatment. The analysis compared the diagnosis of AD as an outcome measure in patients receiving… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 62 publications
(92 reference statements)
3
97
0
2
Order By: Relevance
“…Specifically, disease terms are coded using the Systematized Nomenclature of Medicine-Clinical Terms (SNOMED-CT), a global standard for health terms that provides the core general terminology for EHRs [19]. Previous studies showed that with this large-scale and standardized EHR database, large case-control studies can be undertaken efficiently [20][21][22][23][24], including our recent studies [23,24].…”
Section: Database Descriptionmentioning
confidence: 99%
“…Specifically, disease terms are coded using the Systematized Nomenclature of Medicine-Clinical Terms (SNOMED-CT), a global standard for health terms that provides the core general terminology for EHRs [19]. Previous studies showed that with this large-scale and standardized EHR database, large case-control studies can be undertaken efficiently [20][21][22][23][24], including our recent studies [23,24].…”
Section: Database Descriptionmentioning
confidence: 99%
“…Relatively recently, reports have appeared in the literature about the application of MTX in the treatment of neurological diseases MG [302] and AD (as a drug potentially able to reduce the risk of dementia) [103][104][105][106]. However, these medical experiments have been conducted on small population sizes and, up to now, without significant results, and more detailed studies are needed for determining the conclusive effect of MTX with regards to these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…According to the other research papers, MTX is associated with a lower risk for AD. Based on this knowledge, therapy with MTX shows promise application as a potential treatment for AD [105,106].…”
Section: Methotrexate-based Therapy Of Rheumatoid Arthritismentioning
confidence: 99%
“…Systemic inflammatory diseases such as rheumatoid arthritis (RA), inflammatory bowel disease, and psoriasis, which in part are mediated by TNF ( Fig. 1), heighten risk for AD, and these diseases are also approved indications for TNF blocking agents [15]. If the increased risk of AD is in part due to TNF, then TNF blocking agents could be expected possibly decrease risk of AD.…”
Section: Systemic Inflammation Increases Risk Of Alzheimer's Diseasementioning
confidence: 99%
“…1. Adjusted odds ratio (AOR) for a diagnosis code of dementia associated with a diagnosis for an inflammatory disease compared to the non-inflammatory group disease [15]. AS, ankylosing spondylitis; Crohn's, Crohn's disease; IBD, inflammatory bowel disease; PA, psoriatic arthritis; RA, rheumatoid arthritis; UC, ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%